Synthesis and characterization of calcium copper oxide as anode material for sodium batteries using sol gel method / Nur Syamimi Najihah Md Rusdi - Md Rusdi, Nur Syamimi Najihah (2019)
Calcium copper oxide (CaCuOx) anode material in a sodium-ion battery was synthesized by polyvinyl alcohol (PVA) assisted sol gel-method and its physical characterization was being analysed by using Thermogravimetric Analysis (TGA), Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR). X-ray Diffraction (XRD), Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM/EDS). After the TGA analysis, the calcination temperature for the anode material was determined and 800°C was set up at the furnace. The temperature was chosen as the calcination temperature because the TGA curve becomes flat and no mass loss occurs at temperature above 700°C indicating the completion of the entire reaction. In the ATR-FTIR analysis, the peaks that appear at 458.45 cm-1, 538.88 cm-1 and 547.11 cm-1 is similar to the copper oxygen (Cu-O) bond. After that, the peak that appears is 876.36 cm-1 and related to carbonate ions which is (O-C-O) bond. Last peak appeared in the spectrum is at 1417.58 cm-1 considered as C-O-H bonding. From the SEM/EDS analysis, the morphology of synthesized CaCuOx anode material show uniform and compact surfaces, with no existence of holes or cracks. Agglomerated particles also can be observed. For the XRD analysis, it indicate the synthesized material have high degree of crystallinity. For the elemental composition CaCuOx displays the existence of Ca, Cu, O and C as the major elements in the sample. In this study, the confirmation about electrochemical ability of synthesized CaCuOx anode material cannot be made because no electrochemical characterization was being performed.